Proceedings of the 58th Annual Meeting of the Association for Computational Linguistics 2020
DOI: 10.18653/v1/2020.acl-main.47
|View full text |Cite
|
Sign up to set email alerts
|

Language Models as an Alternative Evaluator of Word Order Hypotheses: A Case Study in Japanese

Abstract: We examine a methodology using neural language models (LMs) for analyzing the word order of language. This LM-based method has the potential to overcome the difficulties existing methods face, such as the propagation of preprocessor errors in count-based methods. In this study, we explore whether the LMbased method is valid for analyzing the word order. As a case study, this study focuses on Japanese due to its complex and flexible word order. To validate the LM-based method, we test (i) parallels between LMs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
(47 reference statements)
0
1
0
Order By: Relevance
“…The importance of word order in LMs has been a topic of debate, with various works claiming that downstream performance is not affected by scrambled inputs (Malkin et al, 2021;Sinha et al, 2021), although it has been shown that LMs are able to retain a notion of word order through their positional embeddings (Abdou et al, 2022). It has been argued that LMs acquire an abstract notion of word order that goes beyond mere n-gram co-occurrence statistics (Futrell and Levy, 2019;Kuribayashi et al, 2020;Merrill et al, 2024), a claim that we in this paper assess for large-scale LMs in the context of adjective order. Finally, numerous works have investigated the trade-off between memorization and generalization in LMs: it has been shown that larger LMs are able to memorize entire passages from the training data (Biderman et al, 2023a;Lesci et al, 2024;Prashanth et al, 2024), but generalization patterns for grammatical phenomena have also been shown to follow human-like generalization (Dankers et al, 2021;Hupkes et al, 2023;Alhama et al, 2023).…”
Section: Word Order In Language Modelsmentioning
confidence: 99%
“…The importance of word order in LMs has been a topic of debate, with various works claiming that downstream performance is not affected by scrambled inputs (Malkin et al, 2021;Sinha et al, 2021), although it has been shown that LMs are able to retain a notion of word order through their positional embeddings (Abdou et al, 2022). It has been argued that LMs acquire an abstract notion of word order that goes beyond mere n-gram co-occurrence statistics (Futrell and Levy, 2019;Kuribayashi et al, 2020;Merrill et al, 2024), a claim that we in this paper assess for large-scale LMs in the context of adjective order. Finally, numerous works have investigated the trade-off between memorization and generalization in LMs: it has been shown that larger LMs are able to memorize entire passages from the training data (Biderman et al, 2023a;Lesci et al, 2024;Prashanth et al, 2024), but generalization patterns for grammatical phenomena have also been shown to follow human-like generalization (Dankers et al, 2021;Hupkes et al, 2023;Alhama et al, 2023).…”
Section: Word Order In Language Modelsmentioning
confidence: 99%